The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11356-017-0443-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical elements as fingerprints of geographical origin in cultivars of Vitis vinifera L. raised on the same SO4 rootstock

Abstract: The uptake of major and trace elements in grapevine (Vitis vinifera L.) can be influenced by soil, climate, geographic origin, and rootstock type. Rootstocks were mainly selected to resist phylloxera and for specific tolerance to lime, mineral uptake, drought, and salinity. The relationship among concentrations of major, trace, and rare earth elements was studied in soil and leaves from two Italian grapevine cultivars, "Cabernet Sauvignon" and "Corvina," employed to produce renowned controlled designation of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…In this study, the elemental concentrations of soil were in similar magnitude as those found by other researchers, with higher levels found in the soils of northern Italy and lower levels in Romania [ 18 , 26 ]. Zou et al [ 28 ] found that Sr had relatively higher levels among trace elements in soils from other seven regions in China, which was consist with our research.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the elemental concentrations of soil were in similar magnitude as those found by other researchers, with higher levels found in the soils of northern Italy and lower levels in Romania [ 18 , 26 ]. Zou et al [ 28 ] found that Sr had relatively higher levels among trace elements in soils from other seven regions in China, which was consist with our research.…”
Section: Discussionsupporting
confidence: 90%
“…In the field of food authentication, MS techniques have several advantages, such as high sensitivity, selectivity, throughput, and multi-analyte capabilities [ 13 , 14 , 15 , 16 ]. Therefore, numerous studies have been dedicated to the application of MS analysis in the provenance of wine [ 12 , 17 , 18 , 19 ]. Unlike the analysis of isotopes with IRMS, multielement analysis with ICP-MS is fast, inexpensive, and extensive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since in organic material the inorganic component is more stable than the organic one, several studies examined trace elements, suggesting the potential application for determination of geographical origin (Almeida and Vasconcelos 2003;Thiel et al 2004;Fabiani et al 2010;Furia et al 2011;Zhao et al 2011;Aceto et al 2013;Versari et al 2014). Other authors focused on geochemical characterization of food products associated with a specific geographical environment for prevention of fraudulent labelling (Nikkarinen and Mertanen 2004;Censi et al 2014;Mercurio et al 2014;Protano and Rossi 2014;Pepi et al 2016Pepi et al , 2017aPii et al 2017).…”
Section: Introductionmentioning
confidence: 99%